2019
DOI: 10.1002/jhet.3819
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, molecular docking simulation, and biological evaluation studies of novel amide and ether conjugates of 2,3‐diaryl‐1,3‐thiazolidin‐4‐ones

Abstract: With an aim to develop potent lead molecules as a novel class of reverse transcriptase (RT) inhibitors, we have synthesized amide and ether conjugates of 2,3-diaryl-1,3-thiazolidin-4-one derivatives. The compounds 9a and 9f exhibited IC 50 values of 0.21113 ± 0.013μM and 12.6804 ± 0.062μM respectively from the in vitro human immunodeficiency virus type 1 (HIV-1) RT assay. None of the compounds showed toxicity towards peripheral blood mononuclear cells (PBMC). Structure-activity relationship (SAR) studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It demonstrated that compound 31 exhibited hydrogen bond interaction of C=O with Lys103, Lys101, and pi‐pi stacking of aromatic group with Trp229. Taking nevirapine as a reference medicine against HIV‐1 RT, substitution at meta position resulted in a potency drop [85] …”
Section: Role Of Nitrogen‐containing Heterocyclic Compounds In Inhibi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrated that compound 31 exhibited hydrogen bond interaction of C=O with Lys103, Lys101, and pi‐pi stacking of aromatic group with Trp229. Taking nevirapine as a reference medicine against HIV‐1 RT, substitution at meta position resulted in a potency drop [85] …”
Section: Role Of Nitrogen‐containing Heterocyclic Compounds In Inhibi...mentioning
confidence: 99%
“…Taking nevirapine as a reference medicine against HIV-1 RT, substitution at meta position resulted in a potency drop. [85] Suryawanshi and teammates created novel 4-thiazolidinone-based compounds and investigated their anti-HIV-1 activity using in-silico and in-vitro study methods. The lead compound showed maximum inhibition activity in TZM-bl assay and PBMC assay using NIH ARRRP reference strain.…”
Section: Thiazolidinone-based Rt Inhibitorsmentioning
confidence: 99%